Valoración de la prescripción de antibióticos en pacientes internados en la Unidad de Cuidados Intensivos de un Hospital Privado en Costa Rica diagnosticados con neumonía - Rodríguez Berrocal, Franklin (2008)
Pneumonia is a lung infection usually caused by several types of bacteria, virus or fungi. The identification of the etiological microorganism is very important to choose the best antibiotic therapy. We made an analysis of the antibiotic strategy applied in a group of community acquired pneumonia or nosocomial pneumonia patients of an intensive care unit in a private hospital in Costa Rica. During the treatment of these patients the physician made several changes of the antibiotic therapy, showing that there are several problems related with the knowledge of the epidemiology and sensitivity of the antibiotics used for this pathology in this hospital. This may cause therapeutically failures, increase patients side effects and longer hospitalization. The introduction of new procedures and information that can help improve the therapy with antibiotics for these patients, their pathologies and every rational-use related issues is necessary.